Uganda Digital Economy Assessment : Country Diagnostic - World Bank (World Bank, Washington, DC, 2021)
Uganda’s digital economy is at a ascent stage of development but there is tremendous opportunity to invest in strategic areas. This Digital Economy for Africa diagnostic presents an overview of digital infrastructure and access, digital entrepreneurship, digital financial services, digital skills and digital platforms in Uganda and identifies key activities that can be undertaken to capitalize on opportunities in the digital economy.